CHANGING CROPPING PATTERN AND ITS SOCIO-ECONOMIC IMPACT ON FARMERS: A COMPREHENSIVE ANALYSIS - Kaur, Anupreet (International Journal of Research -GRANTHAALAYAH, 2025)
The Indian agricultural landscape is dynamic, with cropping patterns constantly evolving due to a complex interplay of factors. This research paper delves into the changing cropping patterns in India, analyzing the driving forces behind these shifts and their subsequent socio-economic impact on farmers. Through a mixed-methods approach, combining quantitative analysis of national-level data with qualitative insights from case studies across diverse agricultural regions, this study aims to provide a comprehensive understanding of the evolving dynamics of Indian agriculture and their implications for farmers' livelihoods, income security, and overall well-being. The paper further explores the role of government policies, technological advancements, and climate change in shaping cropping patterns and offers recommendations for promoting sustainable and equitable agricultural development.